HUBUNGAN KOMORBIDITAS HIPERTENSI DENGAN KEMATIAN PASIEN COVID-19 DI RUMAH SAKIT MUHAMMADIYAH SELOGIRI - Mas’uliyatul ‘Izza; Vina Asna Afifah (STIKES Estu Utomo, 2024)
Background: The high mortality rate in Corona Virus Disease (Covid-19) patients is associated with comorbid conditions. Hypertension is a major comorbidity in hospitalized patients with COVID infection. Therefore, it is important to identify the association between hypertension and the risk of death among people with Covid-9. Objective: To analyze the relationship of comorbid hypertension with the death of Covid-19 patients at Selogiri Muhammadiyah Hospital. Methods: This study is an analytic observational study with a single-center retrospective design. The data collection technique used purposive sampling on secondary data from patient medical records that met the inclusion and exclusion criteria. Respondents of Covid-19 patients were divided into two groups according to comorbid hypertension (n=30) and groups without comorbidities (n=30). Data extraction was carried out to obtain demographic data and clinical data on hospital mortality. The two groups were compared according to demographic features. The association test and the risk of death of Covid-19 patients with comorbid hypertension were tested by Chi Square analysis. Results: The largest age group of the study population was >60 (38.3%) and 33 (55%) patients were male. The mortality rate in the comorbid hypertension group was 14 (46.7%) while in the non-hypertensive comorbid group it was 4 (13.3%). Hypertension comorbidity was significantly associated with the death of Covid-19 patients (p=0.005). Patients with comorbid hypertension had a relative risk of death that was 3.5 (95% CI: 1.3-9.4) greater than those without comorbidities. Conclusion: Hypertension in Covid-19 patients is a variable to predict hospital mortality. Comorbid hypertension is associated with an increased risk of death in Covid-19 patients.